2020
DOI: 10.3389/fphar.2020.587451
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Genetic Markers for Thrombosis in COVID-19 Patients: A Focused Analysis on D-Dimer, Homocysteine and Thromboembolism

Abstract: COVID-19 is caused by Severe Acute Respiratory Syndrome Coronavirus-2, which has infected over thirty eight million individuals worldwide. Emerging evidence indicates that COVID-19 patients are at a high risk of developing coagulopathy and thrombosis, conditions that elevate levels of D-dimer. It is believed that homocysteine, an amino acid that plays a crucial role in coagulation, may also contribute to these conditions. At present, multiple genes are implicated in the development of these disorders. For exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 83 publications
0
39
0
1
Order By: Relevance
“…Homozygosity for the MTHFR 677C>T (rs1801133) variant or compound heterozygosity with 1298A>C (rs1801131) is the most common genetic cause of high homocysteine previously studied in COVID-19 patients 30 . The cut-off value of homocysteine to predict progression of pathological findings in chest CT-imaging of COVID-19 patients was 10.58 µmol/L, compared to the usual definition of high values above 15 µmol/L 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Homozygosity for the MTHFR 677C>T (rs1801133) variant or compound heterozygosity with 1298A>C (rs1801131) is the most common genetic cause of high homocysteine previously studied in COVID-19 patients 30 . The cut-off value of homocysteine to predict progression of pathological findings in chest CT-imaging of COVID-19 patients was 10.58 µmol/L, compared to the usual definition of high values above 15 µmol/L 31 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent report suggested the role of high Hcy levels as a risk factor for severity or complications in COVID-19 [ 16 , 17 ]. Another study showed a significant correlation between Hcy levels and imaging progression on chest computed tomography (CT) from COVID-19 patients [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…As with the highly variable probability of SARS-CoV-2 infection, different populations and individuals will likely respond uniquely to the SARS-CoV-2 vaccine, simply because the main viral antigen inducing pathophysiology associated with infection is the spike glycoprotein, which represents the main viral component in those vaccines that induce VITT, due at least in part to genetic variations. The genetic analysis revealed a list of SNPs and genes that can be used as biomarkers to predict the development of coagulation [ 65 , 66 ].…”
Section: Risk Factorsmentioning
confidence: 99%